An accuracy degradation analysis of ball screw mechanism considering time-varying motion and loading working conditions. (April 2019) - Cheng, Qiang; Qi, Baobao; Liu, Zhifeng; Zhang, Caixia; Xue, Deyi
Highlights: The extended wear model developed based on the Archard wear theory is effective to describe the wear behavior considering the time-varying conditions of contact forces and sliding distances between the balls and the screw/nut raceways for ball screw mechanism (BSM). The developed methods are effective to calculate contact forces and sliding distances between the balls and screw/nut raceways from the time-varying loading and rotational speed of BSM for prediction of the wear of BSM. The accuracy degradation analysis is effective to predict the positioning accuracy error/wear depth from the time-varying loading and rotational speed for BSM. The random wear test scheme of BSM is designed and established under time-varying working conditions. Abstract: Ball screw mechanism (BSM) plays a key role to transmit motion and power in a machine tool. The accuracy of the machine tool is greatly influenced by the accuracy of the BSM. Since accuracy degradation of BSM is primarily due to wear, the wear behavior of BSM is studied considering the time-varying motion and loading working conditions. A new wear prediction model of BSM is introduced in this research considering complex working conditions. Because BSM is subject to dynamic fluctuations of rotational speed and loading in the operation process, a loading model is established to describe the dynamic contact force between the ball and the raceway, and a motion model is developed to describe the dynamic sliding and rolling behaviors between the ball and the raceway. The degradation of BSM accuracy is analyzed considering time-varying motion and loading working conditions. Experiments have also been designed and conducted to demonstrate the effectiveness of the accuracy degradation analysis for BSM.